The Existence of Optimal Distributed Lags - Taylor, L. (Review of Economic Studies, 1970)
Journal Article The Existence of Optimal Distributed Lags Get access Lance Taylor Lance Taylor Harvard University and ODEPLAN, Santiago, Chile Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 1, January 1970, Pages 95–106, https://doi.org/10.2307/2296500 Published: 01 January 1970 Article history Received: 01 January 1969 Accepted: 01 March 1969 Published: 01 January 1970